2021
DOI: 10.1200/jco.2021.39.15_suppl.9021
|View full text |Cite
|
Sign up to set email alerts
|

Tepotinib in patients (pts) with advanced non-small cell lung cancer (NSCLC) with MET amplification (METamp).

Abstract: 9021 Background: METamp is an oncogenic driver occurring in 1–5% of NSCLCs that confers a poor prognosis and lacks approved targeted therapies. Tepotinib, a highly selective MET inhibitor, provided durable response in NSCLC with MET exon 14 ( METex14) skipping in Cohort A of the Phase II VISION trial (NCT02864992). VISION Cohort B evaluated tepotinib in pts with advanced NSCLC and METamp, as detected by a convenient and minimally invasive liquid biopsy assay, in the absence of METex14 skipping. Methods: Pts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…70 New studies on the effect of Tepotinib in NSCLC with MET amplification have shown high and clinically meaningful activity, especially in patients who received Tepotinib in first line, where the ORR was 71%. 71 The most common side effect reported was peripheral edema (7%). 70…”
Section: Actionable Mutations In Lung Cancersmentioning
confidence: 99%
“…70 New studies on the effect of Tepotinib in NSCLC with MET amplification have shown high and clinically meaningful activity, especially in patients who received Tepotinib in first line, where the ORR was 71%. 71 The most common side effect reported was peripheral edema (7%). 70…”
Section: Actionable Mutations In Lung Cancersmentioning
confidence: 99%
“…The cut-offs assessed in the GEOMETRY-mono 1 trial with capmatinib were GCNs of <4, 4 to 5, 6–9 and >10 [ 35 ]. Finally, the most recent analysis from the VISION trial with tepotinib, which utilized liquid biopsy, defined MET amplification positivity as MET GCN > 2.5 [ 86 ].…”
Section: Identifying Patients Most Likely To Benefit From Met -Targeted Therapiesmentioning
confidence: 99%
“…The first analysis presented at ASCO 2021 included 24 patients with MET amplification detected by Guardant360 liquid biopsy assay with MET GCN ≥ 2.5. Response rates in the seven patients that received tepotinib as first-line therapy was 42%, and 30% in the ten patients that were treated using it as second-line [ 86 ].…”
Section: What Are the Preferred First-line And Subsequent Therapies For Advanced Nsclc Patients With De Novo Met Amplimentioning
confidence: 99%
“…In the phase 2 VISION trial, once daily oral tepotinib 500 mg (450 mg active moiety) provided durable clinical responses in patients with advanced NSCLC harboring METex14 skipping alterations [9,10]. The study additionally showed antitumor activity of tepotinib in a separate cohort of patients with NSCLC with MET amplification as a primary driver [11]. Tepotinib is also active in combination with gefitinib in patients with epidermal growth factor receptor (EGFR)-mutant advanced NSCLC and MET-driven resistance to anti-EGFR therapy, as demonstrated in the phase 1b/2 INSIGHT trial [12].…”
Section: Introductionmentioning
confidence: 96%